Brushstrokes of Diplomacy: Where Art Meets International Relations Theory - Singh, Arpita (Universitas Komputer Indonesia, 2025)
Mainstream International Relations (IR) theories such as Realism, Liberalism and Constructivism have traditionally explained state behavior through strategic, institutional, or ideational frameworks. However, these paradigms often underestimate the nuanced role of visual art as a vehicle of soft power. This study explores the intersection of visual art and IR theory and analyzes how art contributes to contemporary diplomatic practices. Through a content analysis of visuals and art in cultural diplomacy, this study found that visual art advances liberal ideals by fostering intercultural dialogue and promoting mutual understanding. It challenges realism’s power-centric narratives by offering alternative and often peace-oriented perspectives on conflicts and negotiations. From a Constructivist viewpoint, art plays a crucial role in shaping national identities and redefining foreign policy orientations. This study further examines India’s evolving deployment of art as a soft power rooted in its rich tradition of cultural dissemination and increasingly present in contemporary diplomatic art. By integrating visual art into IR discourse, this study underscores its strategic relevance as a theoretical construct and a practical diplomatic tool. Keyword: Visual Art, Soft Power, Cultural Diplomacy, International Relations Theory, India